Sizing up physical activity: The relationships between dog characteristics, dog owners' motivations, and dog walking. (May 2016) - Lim, Clarise; Rhodes, Ryan E.
Abstract: Objective: Regular dog walking is likely a symbiotic relationship between the needs of the dog and its owner. This relationship has seen limited attention. The purpose of this study was to examine the relationships between dog characteristics, dog owners' perceptions of responsibility and attachment to their dogs, and the qualities of dog owner exercise motivations (self-determined regulations) with dog walking behavior. Method: Participants were 228 adult dog owners who completed an online survey that included demographics, dog walking, dog responsibility/attachment and exercise regulations. Results: Using mediation procedures, the results showed that the owner's sense of dog walking responsibility and walking relationship was completely mediated by identified (indirect β = .06; bootstrapped lower CI = .02, bootstrapped higher CI = .17) and intrinsic (β = .05; bootstrapped lower CI = .01, bootstrapped higher CI = .15) regulations but these regulations could not account for substantial variance in the dog-related factors. Instead, intrinsic regulation (β = .27), identified regulation (β = .20), dog size (β = .22), and energy level of the dog (β = .13) all contributed to explain 30% of walking behavior. Conclusion: A sense of responsibility to walk the dog, generally the most reliable correlate in past dog walking research, appears to align with more self-determined forms of motivation than controlled. The findings, however, support the premise that dog walking behavior may be a complex mix of human and dog-related factors. This dog and owner relationship may need consideration for successful future dog walking promotion initiatives. Highlights: Dog owners who valued and enjoyed dog walking engaged in more dog walking. Dog owners' engagement in dog walking was not solely based on guilt or duty. Self-determination theory examined dog owner motivation towards dog walking. Owning larger dogs and higher energy dogs resulted in higher levels of walking.